1996
DOI: 10.1136/bjsm.30.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Distant entry pneumothorax in a competitive fencer.

Abstract: An elite level fencer sustained a penetrating wound to the upper arm after his opponent's blade broke. Standard care for a deep puncture wound was given but it was some time before the athlete presented symptoms of a pneumothorax, which was confirmed by radiograph. Although resolution of this case was unremarkable, the possibility of penetrating thoracic injury, even when the point of entry is well outside the thorax and the athlete is not immediately symptomatic, should be born in mind by medical personnel wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…But we agree with Harmer et al [1] who emphasize that the possibility should be envisaged of a penetrating thoracic injury, even when the point of entry is well outside the thorax and the athlete is not immediately symptomatic. Although fencing athletes wear high-performance equipment, we found that there is still an inherent risk of serious injury especially with broken blades.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…But we agree with Harmer et al [1] who emphasize that the possibility should be envisaged of a penetrating thoracic injury, even when the point of entry is well outside the thorax and the athlete is not immediately symptomatic. Although fencing athletes wear high-performance equipment, we found that there is still an inherent risk of serious injury especially with broken blades.…”
Section: Discussionsupporting
confidence: 88%
“…Although fencing athletes wear high-performance equipment, we found that there is still an inherent risk of serious injury especially with broken blades. Recognizing the particular vulnerability of the exposed axilla, which was injured only in one case, rules required wearing of a special plastron, with an extra garment worn under the jacket and designed to cover the upper quadrant of the torso on the fencing arm side [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Each of (D.J Caine, P.A Harmer and M.A Schiff) had confirmed same above by identifying the most related injuries to fencing in Olympic Games, where more studies confirmed that the relative distribution of injuries for the anatomical location of body that most injuries were in the lower limb, especially in the ankle and knee. (3: 125) (6) which is relevant to the weapon type and its relation to the injury occurrence timing that: Foil weapon: the most timing of injuries occurrence during the competitions period reached 52.38% followed by the mid-season training (special preparation) at ratio of 33.33%.…”
Section: Presentation and Discussion Of The Resultsmentioning
confidence: 99%
“…Table (6) shows that the athletic injuries that occurs to the female duelists during all periods of season whether it was at competitions period or the special and general preparation, the most timing of injury occurrence during the competitions period reached 45.28% followed by the mid-season training (special preparation) at ratio of 30.19%.…”
Section: Presentation and Discussion Of The Resultsmentioning
confidence: 99%